(untitled) (Research, Society and Development, 2021)
Population growth, responsible for the growing demand for drinking water, related to pollution and non-rational use of water, results in a scenario of water scarcity in certain regions of all continents, especially in regions of low rainfall. Seeking to reduce the consumption of drinking water for less noble purposes, reduce pressure under water reservoirs and combat water scarcity, the concept of rational use of water emerges. Based on the principles of minimization, separation and reuse, this concept brings with it the suggestion of the use of alternative sources of water, among of them the condensed water from the operation of air conditioners. Such devices work in a way that water condensation occurs, and this effluent is mostly despised. The present work aims to delineate models to estimate the flow of water generated by condensation in air conditioners. The volume of condensed water generated by the devices was measured. Results allowed delineating a mathematical model to determine the flow of this alternative water source, which allows the analysis of the feasibility of its use in a given location for non-potable purposes, such as floor washing, discharges in sanitary basins and irrigation.